(untitled) (Fiep Bulletin - online, 2012)
The article presents some data from an intervention research developed in LAR (Laboratory of Ludo-Recreational Activities) and by members of GEIPEE (Group of studies, intervention ans research in scholar education). The main objective of the Intervention is create conditions on the didactic-pedagogic and ludo-educational intervention, through the physical education contents, specially plays, toys and games, for special children. The intervention has been developed inside of LAR and its main objective is creating teaching and lerarning activities in an ludo-educational way, to help disabled children whose have special needs of education. At the same that we work with the children inside the LAR, the project offer guidance to parents and teachers about the process of human development, in a historical-cultural approach and about special methodologies for teaching at the school, traying to ohelp parents and teachers how to handlle with special children in everyday life. One of the most important issue is to the project is to provide a dialogue with the teachers who work directly with children at school, to build and implement special methods of teaching in school, thus promoting an understanding of the learning process and the real contribution to a full human development inside the school. To start the investigation 17 (seventeen) Interviews were conducted with the teachers whose children participate in the LAR activities. We selected 03 (three) interviews questions to presente in this work, which has as central theme (full development and behaviors) that the teachers answered about disability and/or difficulties of their childrens and also, teachers’ views on inclusive education, and about the teaching strategies and resources to handle in the school. The data obtained from the interviews point the necessity for changes in teaching practices, however, claim for educational and pedagogical resources and development of professionals skills inside the school environment to improve teachers actions. The teachers asked for having a continuous training for working with special needs childrens and emphasize the urgent continuing education on strategies and teaching methods and also methodologies for working with individuals with special needs. In our view, it should be the task of the state government and municipal departments of education and public universities to work together to build a new perspective for the teaching and learning in schools for special needs children and in this way to build as inclusive school and an inclusive society.